2008
DOI: 10.1172/jci33716
|View full text |Cite
|
Sign up to set email alerts
|

Can you hear me now? A genetic model of otitis media with effusion

Abstract: Otitis media with effusion (OME) is characterized by the occurrence of fluid in the middle-ear cavity in the absence of any signs of acute ear infection and occurs most frequently in children with auditory or eustachian tube dysfunction. Its chronic form is an important clinical issue for pediatricians and otologists alike. The study by Depreux et al. in this issue of the JCI shows that absence of the transcriptional activator Eya4 in knockout mice results in abnormal structuring of the eustachian tube, thus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Risk factors for OM include infection, altered immune status, exposure to tobacco smoke, and anatomical defects such as cleft palate [ 14 ] . In addition, although the pathogenesis of OM is multifactorial, a role for genetic predisposition is increasingly recognized [ 15 , 16 ]. In 22q11DS, studies have shown that a majority of patients have a history of chronic or recurrent OM [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for OM include infection, altered immune status, exposure to tobacco smoke, and anatomical defects such as cleft palate [ 14 ] . In addition, although the pathogenesis of OM is multifactorial, a role for genetic predisposition is increasingly recognized [ 15 , 16 ]. In 22q11DS, studies have shown that a majority of patients have a history of chronic or recurrent OM [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using murine models, a crucial role for proteins in the Toll receptor pathways was identified. [69][70][71] A mouse model of deafness known to develop chronic suppurative OM, Jeff, carries a mutation in an F-box gene, Fbxo11, predisposing to development of cleft palate. 54,60 Indeed, defects in chemokines such as IL-8, MCP-1 and CCL3, which play integral roles in promoting early neutrophilic inflammation, [63][64][65] can predispose animals to AOM.…”
Section: Eustachian Tube Obstructionmentioning
confidence: 99%